Description of a new species of stilt-legged mite of the genus Neophyllobius Berlese (Acari: Camerobiidae) from Peru - Escobar-Garcia, Hector Alonso [UNESP] (2023)
A new species of Neotropical Camerobiidae from Peru, Neophyllobius (Neophyllobius) unpensissp. nov. is described from the leaves of a native forest tree of Neltuma piurensis (Fabaceae), based on females and protonymphs. The new stilt-legged mite was found in the spring, summer, and autumn, but were more frequently observed during summer. http://zoobank.org/urn:lsid:zoobank.org:pub:68C44B2D-096B-4990-9097-AFB69580508A http://zoobank.org/urn:lsid:zoobank.org:act:AD816CB2-CB3E-4C21-A962-66AA5C1E1726.